Lived experiences of primary caregivers of persons with disability during the Covid-19 pandemic - Romero, Divine P. (Animo Repository, 2021)
The COVID-19 pandemic is an extremely difficult situation to experience due to the host of many healthcare protocols such as the implementation of quarantine restrictions to contain the proliferation of the virus. As a result of these restrictions, it equally promoted fear of being infected, financial uncertainties, and grief and loss of those who have lost loved ones, and many other physical and psychological consequences of the stay-at-home policy. Consequently, primary caregivers of Persons With Disability (PWD) strive harder to make adjustments to sustain their family and PWD members’ needs the primary caregivers face. Hence, the need to examine their current situation and experiences in this time of the COVID-19 pandemic is essential to seek ways to improve the quality of their lives at this time of crisis. This research is a qualitative design using a case study method exploring the lived experiences of the primary caregivers of the PWDs during the COVID-19 pandemic. The respondents of the study consisted of five (5) primary caregivers using a snowball sampling technique as the collection data procedure. The data were collected using semi-structured in-depth interviews and were analyzed using thematic analysis. The results of the interviews showed four main themes derived from the narratives of primary caregivers’ lived experiences. These categories were access to healthcare and other resources, cost of caregiving, family living conditions, and coping strategies.